REVIEW OF BIOMATERIAL - Rahane Santosh Prabhakar (International Journal of Innovations in Engineering Research and Technology, 2021)
Biomaterials are in the form of implants like sutures, bone plates, joint replacementsas well asmedical devices like pacemakers, artificial hearts, blood tubes are widely used to replace and/or restore the function of traumatized or degenerated tissues or organs, and thus improve the quality of life of the patients. The first and foremost requirement for the choice of biomaterial is its acceptability by the human body. A biomaterial used for implant should possess some important properties in order to long-term usage in the body without reaction. The most common classes of biomaterials used as biomedical material like metals, Polymers, ceramics and composites. These four classes are used singly and in combination to form most of the implantation devices available today. This review will be of value to researchers who are interested in the state of the art of biomaterial evaluation and selection of biomaterials.